An in-silico approach to predict and exploit synthetic lethality in cancer metabolism - Iñigo Apaolaza (Nature Portfolio, 2017)
Exploiting synthetic lethality is a promising approach for cancer therapy. Here, the authors present an approach to identifying such interactions by finding genetic minimal cut sets (gMCSs) that block cancer proliferation, and apply it to study the lethality of RRM1 inhibition in multiple myeloma.